Brucella dissociation is essential for macrophage egress and bacterial dissemination - Ficht, Thomas A.; Pei, Jianwu; Kahl-McDonagh, Melissa (Frontiers in Cellular and Infection Microbiology, 2014)
It has long been observed that smooth Brucella can dissociate into rough mutants that are cytotoxic to macrophages. However, the in vivo biological significance and/or mechanistic details of Brucella dissociation and cytotoxicity remain incomplete. In the current report, a plaque assay was developed using Brucella strains exhibiting varying degrees of cytotoxicity. Infected monolayers were observed daily using phase contrast microscopy for plaque formation while Brucella uptake and replication were monitored using an immunofluorescence assay (IFA). Visible plaques were detected at 4–5 days post infection (p.i.) with cytotoxic Brucella 16MΔmanBA at an MOI of 0.1. IFA staining demonstrated that the plaques consisted of macrophages with replicating Brucella. Visible plaques were not detected in monolayers infected with non-cytotoxic 16MΔmanBAΔvirB2 at an MOI of 0.1. However, IFA staining did reveal small groups of macrophages (foci) with replicating Brucella in the monolayers infected with 16MΔmanBAΔvirB2. The size of the foci observed in macrophage monolayers infected with rough Brucella correlated directly with cytotoxicity measured in liquid culture, suggesting that cytotoxicity was essential for Brucella egress and dissemination. In monolayers infected with 16M, small and large foci were observed. Double antibody staining revealed spontaneous rough mutants within the large, but not the small foci in 16M infected monolayers. Furthermore, plaque formation was observed in the large foci derived from 16M infections. Finally, the addition of gentamicin to the culture medium inhibited plaque formation, suggesting that cell-to-cell spread occurred only following release of the organisms from the cells. Taken together, these results demonstrate that Brucella-induced cytotoxicity is critical for Brucella egress and dissemination.